Interference and diffraction effects generated by multiple apertures (2004)
ABSTRACT: The effects of interference and diffraction produced by a bidimensional structure composed of multiple and identical apertures are studied. The apertures have different shapes, sizes and spatial distribution. Such effects are competitive during the propagation, that is, in some planes the interference effects are more visible, while in others prevail the diffraction ones.